AN ANALYSIS ON THE FACTORS WHICH INFLUENCE REVENUE OF HEALTH CARE RETRIBUTION BY APPLIYING BLUD FINANCIAL MANAGEMENT PATTERN AS MODERATING VARIABLE AT RSUD KARIMUN REGENCY - junaldi, junaldi (Asosiasi Dosen Akuntansi Indonesia, 2018)
The purpose of this research is to analyze the influence of the quality of health services, human resource competence and the number of patient visits to the income levies health services at general hospital of Karimun Regency and to know and analyze the influence of the implementation of financial management pattern of public service agency. The type of this research is quantitative with associative causal method. This research was done using survey methods to disseminate the questionnaire and interview to all employees of general hospital of Karimun Regency. The population in this research is all employees at general hospital of Karimun Regency numbered as many as 472 people. The number of sample as many as 143 people. The data has been analyzed using multiple linear regression analysis and residual test. The results of this research showed that simultaneously the quality of health services, human resource competence and the number of patient visits significant effect against the acceptance of retribution health services. Partially the quality of health services, human resource competence and the number of patient visits have positive and significant impact on the income levies health services. financial management pattern of public service agency may moderate the relationship between the quality of health services, human resource competence and the number of visits patients with income levies health services at general hospital of Karimun Regency.